Foliar application of nano zero-valent iron improves the fruit quality of ‘Yanfu No.6’ apple - Yang Lu; Yongjuan Cheng; Guanquecailang Lan; Guoping Liang; Zhiyuan Bian; Zonghuan Ma; Juan Mao; Baihong Chen (BMC Plant Biology)
Abstract Background In recent years, the apple industry in Jingning County has developed rapidly. However, due to the neglect of the importance of trace elements in apple cultivation, iron chlorosis often occurs in fruit trees, affecting the growth of the industry. This study investigates the effects of different concentrations of nano-zero-valent iron (nZVI) on apple tree growth and fruit aims to provide theoretical references for determining the optimal nZVI concentration to improve the quality of Jingning apples. Results This study systematically analyzed the effects of different concentrations of nanoscale zero-valent iron (nZVI) on the growth and fruit quality of ‘Yanfu No.6’ apple trees. The experimental results showed that compared with the control group (CK), the T2 treatment group at a concentration of 10 mg L⁻¹ significantly promoted the growth of apple tree shoots, as evidenced by an increase of about 15% in shoot length and a 10% increase in base diameter (p < 0.05). At the same time, this concentration treatment significantly improved the photosynthesis rate, SPAD value, and enzyme activities of apple leaves, including peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT), and the enhancement effect remained stable at multiple time points. Furthermore, the T2 treatment at a concentration of 10 mg L⁻¹ significantly improved the appearance quality and intrinsic quality of apple fruit, specifically by increasing fruit weight, achieving a coordinated ratio of fruit diameter, having moderate hardness, and increasing soluble protein and vitamin C content. Conclusion In this study, the appropriate concentration of nZVI promoted the growth and fruit quality of “Yanfu No.6” apple tree, among which, the nano-zero-valent iron with a concentration of 10 mg L− 1 had a significant effect on the growth and development of “Yanfu No.6” apple. This finding not only provides a theoretical basis and practical guidance for the application of nZVI in fruit tree production, but also provides a useful reference for the production of other fruit trees and crops. However, future studies are needed to further explore the regulation mechanism of nZVI on fruit tree growth and the molecular mechanism of its effect on fruit quality. Meanwhile, the environmental risk assessment and safety studies of nZVI should be strengthened to ensure its sustainable application and reduce the potential risks. These studies will provide a more comprehensive and in-depth scientific support for the widespread application of nZVI in agricultural production.